Cultura de paz, educação e a prática extensionista: análise da ação reiki na FACED, no contexto da Pandemia de Covid – 19 - Melo, Isabel Cristina Carlos Ferro (2025)
This study investigates the implementation of the promotion of the Culture of Peace at the Federal University of Ceará (UFC), based on an analysis of the Reiki extension program at the Faculty of Education (FACED), in the context of covid-19, from the perspective of the executing team, in this case, the reiki therapists. This activity was carried out during the FACED ACOLHE action and is linked to the extension project Culture of Peace at FACED: Education, Spirituality and Health Actions, promoted by the Culture of Peace, Education and Spirituality Group, under the coordination of Professor Kelma Matos. Specifically, the research considers how Integrative and Complementary Health Practices, precisely reiki therapy, collaborate to promote a culture of peace at UFC/FACED; identifies the effects, impacts and changes (or lack thereof) observed in the implementation of reiki at FACED during the coronavirus pandemic, as well as its relationship with the culture of peace and; describes the contributions that this spirituality theme presents as an extension activity to promote a culture of peace. To this end, the theoretical bases are supported by studies of the theories of Barros (2007), Boff (1999;2001), De’ Carl (2014), Diskin (2008), Domingues e Magalhães (2022), Jares (2002), Matos (2016;2019), Nascimento (2009;2019), Severino (2007), followed by an exploratory, documentary and bibliographic study, with the research strategy being the case study. This research shows, through the statements of the 13 interviewees, that despite the challenges of access to PICS, even beyond the university, the relevance of the role of university extension activities is immeasurable, presenting itself as an important means of articulation with the UFC's internal and external academic community. The Reiki action at FACED is understood as a means of promoting a culture of peace at the UFC, since it uses “caring for the other” as the main technique for applying reiki, which does not impose conditions and is a practice of a culture of peace.